Statement of Expert in Holding Special Cases at the Investigation Stage Based on Perkap 6 of 2019 Concerning Investigation of Criminal Acts - Anang Shophan Tornado (International Journal of Law, Environment, and Natural Resources, 2022)
As a form of implementation as a rule of law state, law enforcement officers consisting of police, prosecutors, judges and lawyers are presented to carry out this function. The police as one of the law enforcers carry out security measures in the community, in every action they are subject to formal law, namely the Criminal Procedure Code (KUHAP). In the Criminal Procedure Code, the task of the police to disclose a crime or also called a crime is known as an investigation. In the investigation stage which aims to make light of a crime and find the suspect by collecting evidence, of course, must go through the correct and accountable procedures. A little wrong in carrying out the procedure, the investigator as a user in the investigation in his actions makes it clear that the crime must collect evidence that can really be tested in quality. In the Criminal Procedure Code, evidence is contained in Article 184 paragraph (1) which consists of witness statements, expert statements, letters, instructions and statements of the accused. As for the evidence that is in the spotlight in the expert's statement, where the expert's statement is evidence that is felt to play a significant role in determining the elements of the crime which in the end can shed light on the crime in the investigation stage. KUHAP as the holy book of criminal law practitioners in enforcing criminal law is certainly expected has all the facilities or in other words can accommodate all the sense of justice for the parties involved in it. As we also know that the Criminal Procedure Code was born in 1981, if we feel that he is already 40 years old, if we equate it with human age, it can be said that he is entering adulthood. The maturity of the KUHAP so far can be marked by the persistence of the Criminal Procedure Code as the basis for law enforcement and justice seekers in criminal cases even though there are patchworks here and there in the form of implementing regulations and in the form of a Supreme Court Circular to provide perfection and fulfill the people's sense of justice.